Reinforcing Your Roof - Hal S. Knowles, III; Kathleen C. Ruppert; Karla A. Lenfesty; Barbara Haldeman (EDIS, 2007)
ABE-377, a 2-page fact sheet by Hal S. Knowles, III, Kathleen C. Ruppert, Karla A. Lenfesty, and Barbara Haldeman, is part 4 in the Education + Action = Wind Damage Mitigation series. It discusses roof design/bracing/installation and creating a continuous load path to strengthen your home against windstorms. Published by the UF Department of Agricultural and Biological Engineering, November 2005.